Efeito da rigidez de pilar parede no comportamento sísmico de edifício de concreto armado - Thölken, Denise (2013)
The aim of this work is to study the stiffness effect of wall columns on structural behavior of reinforced concrete buildings subjected to seismic action. The premises of the Brazilian standard ABNT NBR14521:2006 were considered, which presents criteria for earthquake resistant design of structures. The linear analysis employed the methods of the Brazilian standard - equivalent static load method, response spectrum analysis and time history method - were applied to buildings with two types of structural systems, namely concrete frame and dual system concrete frame and wall columns. The results were analyzed in edge frames structures in the longitudinal and transverse directions, comparing the displacement of each floor and shear, bending moment and axial forces on the bases of the columns. A comparison was made between the three methods applied and the structural systems analyzed.